Sablot (Litsea glutinosa) Lour. Rob.: Bringing it Back to the Landscape - Rabena, Alfredo R. (JPAIR Multidisciplinary Research, 2008)
Sablot (Litsea glutinosa) Lour. Rob. Leaves of a multipurpose tree belonging to the Lauraceae family, an original component of plastering in the construction of brick houses in the old Ciudad Fernandina now Vigan City in Ilocos Sur, Philippines is fast disappearing due to urbanization and many factors. This study determined the versatility of sablot (Litsea glutinosa) in order to bring back its use in the plastering industry. New frontiers in the discovery of the multipurpose tree showed medicinal value. Phytochemical analyses of sablot leaves showed antimicrobial properties against bacteria. Products like extracts formulated into ointments were derived from both leaves and barks manifested high growth inhibitions. Propagation techniques using seeds, cuttings, propagation by transplanting and by marcotting and other experimental strategies are studied to bring back sablot (Litsea glutinosa) to the landscape for human livelihood specially in the tropical rural areas of Ilocos of the Philippines. The primary objective of this study is to account the many uses of sablot both indigenous practices as well as new discoveries in order to fully utilize its potentials.